Healthcare Bioethics: A Vital Branch of Bioethics and a New Possible Pillar for Modern Healthcare Systems Strengthening Worldwide - Nzayikorera, Janvier (Journal of Community Medicine and Health Solutions, 2023)
Globally, all people deserve the highest level of respect for their dignity, rights, and health. Bioethics has been recognized as a powerful discipline that aims to ensure such respect. Fritz Jar (1895–1953) and Van Rensselar Potter (1911–2001) will remain heroic men who ushered in the existence of the discipline of bioethics. Bioethics has been recognized as the science of survival and a bridge to the future. Thus, bioethics aims to enrich people’s wisdom. Wisdom is the knowledge of how to use knowledge for human survival and improvement in the quality of life. Worldwide, all people must widely possess such knowledge. Unfortunately, after many years of existence, implementing the principles and goals of bioethics remains centralized and confined to academic fields. Due to its centralized status, few branches of bioethics have been recognized. Besides, both pre-standard and standard practices still exist in the field of bioethics. Healthcare bioethical principles have been mentioned in numerous publications. However, healthcare bioethics has not been recognized as a vital branch of bioethics. The lack of well-established healthcare bioethics hinders strategies for eradicating many of the ephemeral and heuristic approaches that are still obstructing the achievement of optimum health status for numerous people worldwide. Integrating bioethical principles in all healthcare sectors in decentralized manners would lead to the existence of healthcare bioethics. The purpose of this manuscript is to describe healthcare bioethics as a vital branch of bioethics with respect to its description, branches, core principles, functions, system components, and pre-standard and standard practices of healthcare bioethics.